Managing iatrogenic aortic dissection during primary percutaneous coronary intervention of the left main stem. Issue 5 (16th February 2022) - Sherif, Mohamed; Jhala, Hiral; Chetty, Govind
Abstract: Iatrogenic aortic dissection post primary percutaneous coronary intervention (PCI) is rare but yet a serious complication. In this report, we present a case of a 40‐year‐old lady who had an aortic dissection post PCI which was initially missed by the conventional contrast images and required a gated computerized tomography aortogram to confirm the diagnosis. The patient was managed with strict blood pressure control resulting in complete healing of the dissection after 72 hours of the management. The case illustrates the importance of selecting the correct imaging to make an accurate diagnosis when aortic dissection is suspected and outlines the importance of blood pressure control in treating iatrogenic aortic dissections.